2019
DOI: 10.1038/s41467-019-12458-1
|View full text |Cite
|
Sign up to set email alerts
|

A nanofluidic device for parallel single nanoparticle catalysis in solution

Abstract: Studying single catalyst nanoparticles, during reaction, eliminates averaging effects that are an inherent limitation of ensemble experiments. It enables establishing structure–function correlations beyond averaged properties by including particle-specific descriptors such as defects, chemical heterogeneity and microstructure. Driven by these prospects, several single particle catalysis concepts have been implemented. However, they all have limitations such as low throughput, or that they require very low reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…Most gold nanozyme studies reported in the literature are based on AuNPs synthesized using bottom-up approaches due to their low-cost and facile syntheses. However, gold nanostructures exhibiting catalytic properties have also been fabricated through top-down approaches [90][91][92]. Cao et al [90] found that these properties could be improved by fabrication of nanostructured arrays on Au thin film.…”
Section: Catalytic Properties Of Gold Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most gold nanozyme studies reported in the literature are based on AuNPs synthesized using bottom-up approaches due to their low-cost and facile syntheses. However, gold nanostructures exhibiting catalytic properties have also been fabricated through top-down approaches [90][91][92]. Cao et al [90] found that these properties could be improved by fabrication of nanostructured arrays on Au thin film.…”
Section: Catalytic Properties Of Gold Nanoparticlesmentioning
confidence: 99%
“…Electron beam lithography has also been used to fabricate a nanofluidic device consisting of 11 sets of 5 nanochannels, each decorated with a set of single-Au nanoparticles with identical size. These NPs were grown through Au evaporation and used for the reduction of fluorescein as a model reaction [91]. Also arrays of electrically driven plasmonic nanorods have been used for catalytic purposes, as the numerous resulting tunnel junctions favour the generation of hot electrons, facilitating strongly confined chemical reactions.…”
Section: Catalytic Properties Of Gold Nanoparticlesmentioning
confidence: 99%
“…This ensures that the obtained single particle results can provide the anticipated guidance for improving the performance of real catalysts, which naturally are composed of a large ensemble. To this end, the demonstrated use of nanofluidic structures in single particle catalysis in the gas phase also constitutes the first application of the nanofluidics paradigm to a gaseous fluid in general and therefore goes substantially beyond its recently introduced liquid-phase counterpart (18).…”
Section: Introductionmentioning
confidence: 99%
“…In response, we introduce highly multiplexed operando single particle plasmonic nanoimaging in combination with our recently developed nanofluidic reactor platform 24,25 that enables online mass spectrometry from extremely small amounts of catalyst material. As the key advance, we demonstrate how this concept is able to combine single particle resolution in catalyst state dynamics imaging from a quasi-2D array of 1000 nominally identical Cu nanoparticles that constitute the whole catalyst bed, with online quadrupole mass spectrometry (QMS) from the same particles.…”
mentioning
confidence: 99%